Strategi Pembelajaran PAI Terhadap Pembentukan Karakter Siswa di SD Negeri 3 Sampang Kecamatan Sempor - Ayu Rodziyah; Eliyanto Eliyanto; Nginayatul Khasanah (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to: (1) Knowing the strategy of PAI teachers in shaping the character of students at SD Negeri 3 Sampang Sempor. (2) knowing the character values ​​instilled by PAI teachers at SD Negeri 3 Sampang Sempor. In an effort to achieve the specified goals, the researchers applied a qualitative approach with field methods. Several methods of collecting data were applied by the researchers, namely the interview, observation, and documentation methods. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The research that has been done shows the results: (1) PAI teacher strategies in shaping student character by: First, exemplary behavior. Second, the cultivation of a disciplined attitude. Teachers act decisively in giving verbal warnings and even strict sanctions for those who violate school rules. Third with habituation. Habituation programs in schools such as: Praying Duha in congregation. Fourth, by building a conducive climate. Fifth, with integration and internalization. Integrating character values ​​in each subject, which focuses on Islamic Religious Education material. (2) character values ​​instilled by PAI teachers at SD Negeri 3 Sampang Sempor are as follows: a) honesty b) religious c) discipline d) cleanliness and neatness e) caring f) responsibility g) curiosity h) and trust self.